(untitled) (INNOVATIVE ECONOMY, 2019)
Shapoval V.M., Herasymenko Т.V. INCREASING THE EFFICIENCY OF USING ECONOMIC POTENTIAL OF ENTERPRISES OF TOURIST COMPLEX Purpose. The aim of this article is to substantiate the approach to the study of the effectiveness of using the economic potential of the tourist complex enterprises, identifying the factors of its increasing, taking into account the conditions of the current stage of the Ukrainian economy. Methodology of research. Theoretical and methodological basis of the study are research and development of Ukrainian and foreign scientists, associated with economic problems of enterprises of tourist complex and ways of their solutions, legislative and regulatory acts of Ukraine in this field, the specialized materials of scientific conferences and symposia. The study used the following methods: grouping – to determine the main tasks of enterprises of the tourism sector in the framework of the new approach to the use of economic potential; generalizations - to build a concept of the economic potential of enterprises in the tourism sector from the perspective of a comprehensive assessment of the effectiveness of the travel agency. Findings. The methodological approaches to the functioning and assessment of the economic potential of enterprises in the tourism industry are summarized and systematized in the article based on the domestic and foreign experience. A mechanism for the effective functioning of the economic potential of enterprises in the tourism sector, taking into account the peculiarities of the activities of its subjects in the formation and use of the resource potential, is proposed. A system of interacting indicators of resources and results has been developed, allowing to substantiate key indicators for assessing the economic potential of enterprises in the tourism sector. The directions of increasing the efficiency of use and the development of the economic potential of tourist enterprises have been proposed. Originality. The originality lies in the determining the directions of increasing the efficiency of using the economic potential of enterprises in the tourism sector, which allow to determine the reserves of economic growth, and includes methods, tools and directions for solving the tasks of strategic development of economic potential. Practical value. The results of the study are the basis for solving practical problems in determining the reserves of economic growth tourism enterprises that can improve the competitiveness of the industry. Key words: economic potential, enterprises of tourist complex, resource potential, assessment of the effectiveness, factors affecting the efficiency, Indicators of the effectiveness.